Who’s watching your money? : - Waymire, Jack (Wiley, 2004)
Who’s Watching Your Money? is an invaluable guide for the millions of investors who have either unknowingly selected a poor-quality advisor or have yet to find someone to help them achieve their financial goals. Filled with in-depth insights and expert advice, this book skillfully describes the problems associated with finding, evaluating, selecting, and monitoring a financial advisor. To guide you on your journey, Who’s Watching Your Money? outlines "The 17 Paladin Principles." These proven principles–developed by author Jack Waymire–provide a summary solution that will dramatically increase the probability of finding a quality advisor to help secure your financial future.